SPY: A new scission point model based on microscopic ingredients to predict fission fragments properties - Lemaître J.-F.; Dubray N.; Hilaire S.; Panebianco S.; Sida J.-L. (EPJ Web of Conferences, 2013)
Our purpose is to determine fission fragments characteristics in a framework of a scission point model named SPY for Scission Point Yields. This approach can be considered as a theoretical laboratory to study fission mechanism since it gives access to the correlation between the fragments properties and their nuclear structure, such as shell correction, pairing, collective degrees of freedom, odd-even effects. Which ones are dominant in final state? What is the impact of compound nucleus structure? The SPY model consists in a statistical description of the fission process at the scission point where fragments are completely formed and well separated with fixed properties. The most important property of the model relies on the nuclear structure of the fragments which is derived from full quantum microscopic calculations. This approach allows computing the fission final state of extremely exotic nuclei which are inaccessible by most of the fission model available on the market.